Functional basketball analysis (overview) - Kocic, M.; Beric, D.; Nikolic, D.; Mitic, M.; Stanišic, Z. (XX Scientific Conference in physical education, sport and recreation - (Nis, Serbia, october 19-21st, 2017) - Book of Proceedings, 2017)
The modern basketball game is characterized by high intensity of activity for all forty minutes of its duration. Requires players to undergo their own abilities to the collective as well as a wide range of basic and specific functional and motor skills. It is almost impossible to isolate some skill that does not partially participate in the success of the game. Examination of basic and specific functional and motor skills provides an insight into the qualitative and quantitative characteristics of basketball players of different positions in the team, as well as the different ranking of the competition. The aim of this study was the analysis of the research in which parameters of functional capabilities were evaluated and their impact on success in the basketball game.The research included 21 papers published in the period from 2000 to 2015. The descriptive method and theoretical analysis were used to collect, classify and analyze the targeted research, and the research that they came across were: Google, Google Scholar, PubMed and Kobson. The results showed that the use of diagnostic tools is necessary especially in professional basketball, because without them the exact condition of the training of a basketball player regarding the parameters of functional abilities can not be reached. The choice of tests to assess them depends on many factors, such as age, level of training, availability, number of respondents, etc.